Higher-order interaction effects among operating conditions and feedstocks shape reactor microbiomes and fatty acid production profiles - Jorge L. Rico; Amanda Schmidt; Parsa Ghadermazi; Kristen Otto; Jessica L. Metcalf; Jorge Saul Castillo Jaimes; Siu Hung Joshua Chan; Kenneth F. Reardon; Susan K. De Long (Bioresource Technology, 2026)

Ensuring adaptability and applicability of long-term contaminant monitoring initiatives: A discussion of NOAA’s National Mussel Watch Program current practices and future approaches - N. A. Castillo; L. M. Swam-Jaramillo; M. M. Rider; A. Morozova; K. L. Kimbrough; E. D. Davenport; M. A. Edwards; F. Arzayus; D. A. Apeti (Environmental Monitoring and Assessment, 2026)

Strengthening national genebanks through genomics and regional collaboration: Lessons from Latin America and the Caribbean - M. Carvajal-Yepes; C. Petroli; M. Correa; F. Breseghello; G. Tapia; E. Salazar; A. Chassaigne; M. Ferreyra; P.H. Reyes-Herrera; M. Guzmán; A. Mendoza; R. Vidal; et al. (Global Food Security, 2026)

Functional analysis of wssv025 gene in the pathogenicity of white spot syndrome virus in Penaeus monodon - Shanel G. Manito; Cong-Yan Chen; Brandon Rafael de Jesús Castillo-Corea; Mary Nia M. Santos; Casiano H. Choresca; Fiona L. Pedroso; Christopher Marlowe Caipang; Han-Ching Wang; Fernand F. Fagutao (Fish & Shellfish Immunology, 2026)

Sex matters: female black corals experience higher stress under different current velocities - L. Palacios-Castillo; S. Navarro-Mayoral; M. Godefroid; C. García-Herrera; F. Tuya; R. Haroun; F. Otero-Ferrer (Coral Reefs, 2026)
Black coral forests play a vital role in mesophotic and deep-water environments, providing habitat and refuge for numerous organisms. Their presence and distribution are influenced by hydrodynamic conditions. Yet, insight into the effect of current velocity on the survival and overall condition of black corals, and how this may differ between sexes during the reproductive period, is lacking. Here, we investigated how the current velocity affected male and female nubbins of Antipathella wollastoni , throughout a 5-week experiment, under three treatments: no (0 cm s −1 ), low (mean ± SE = 5.3 cm s −1 ± 0.27) and high current (10 cm s −1 ± 0.42). We studied both the nubbin state ( i.e. mortality, tissue necrosis and propagule production) and their physiology ( i.e. total antioxidant capacity, TAC). We found higher tissue necrosis and mortality in the no-current treatment. Responses were significantly sex-conditioned across all treatments. All male nubbins survived the experiment and exhibited minimal tissue necrosis (mean ± SE = 4.72% ± 0.77), whereas 33.3% of female nubbins died and showed significantly higher tissue necrosis (37.05% ± 8.57). Propagule release was up to fourfold higher under high current compared to low, whereas nubbins in the no-current treatment produced almost none, likely due to the rapid onset of necrosis preventing the use of this escape response. The findings emphasize the importance of current velocities to rear black corals under controlled conditions, especially given the increased vulnerability of female nubbins during the reproductive period.

Simultaneous consumption of Liolaemus lizards by the raptor Geranoaetus polyosoma in south-central patagonia - Candela Victorel; Martín C. Castillo; Mauro I. Bonavita; Mauro N. Tammone; Laura M. Casalins; Laura Mangini Mas; Valeria S. Ojeda; Débora L. Moreno Azócar; Marcelo F. Bonino; Félix B. Cruz (acta ethologica, 2026)

Long-Term Treatment with Alcaligenes faecalis A12C Improves Host Resistance to Pathogens in Septic Rats: Possible Contribution of Curdlan-Like Immune Trainer - C. J. Martel-Benítez; R. Alayón-Afonso; D. Padilla Castillo; F. J. Chamizo-López; M. Isabel García-Laorden; A. Espinosa de los Monteros y Zayas; J. C. Rivero-Vera; P. Nogueira Salgueiro; F. Real; A. Bordes-Benítez; A. Martel Quintana; C. Almeida Peña; et al. (Probiotics and Antimicrobial Proteins, 2025)
Curdlan, a β-1,3/1,6-glucan found in Alcaligenes faecalis ( A. faecalis ) wall, activates innate and humoral immunity. The aim of this study is to evaluate whether pretreated rats with A. faecalis A12C could prevent sepsis disturbances and identify the immunomodulatory mechanisms involved. Experiments occurred in two stages: a survival study with 16 rats randomly divided into septic (SC) ( n = 8) and septic pretreated (SA) ( n = 8) groups and 45 rats divided into four groups: healthy (AGUSAN) ( n = 9), septic (AGUIC) ( n = 13), septic pretreated (AGUIA) ( n = 14), and healthy pretreated (AGUSTO) ( n = 9). Sepsis was induced by cecal ligation and puncture after 30 days of A. faecalis A12C pretreatment or without. SA group had a higher survival rate of 58% vs. 16% for SC group ( P < 0.05). Overall, AGUIA showed better status than AGUIC ( P < 0.01). Higher monocytosis was found in AGUIA and AGUSTO vs. AGUIC and AGUSAN, respectively ( P < 0.05). A gradual increase in curdlan fecal concentration was observed in AGUIA during pretreatment. Fecal concentrations of Escherichia coli significantly decreased in AGUIA and AGUSTO. Bacterial load in urine, peritoneal lavage fluid (PLF), and bronchoalveolar lavage fluid (BALF) decreased ( P < 0.05) in AGUIA vs. AGUIC. Finally, lower inflammation was observed in serum, BALF, and PLF, with reduced IL-6, IL-10, IL-1β, and TNF-α, along with less damage in lungs and peritoneum in AGUIA vs. AGUIC. These findings suggest the connection between curdlan—produced by A. faecalis A12C—with the immune system and the reduction in severity of experimental sepsis.

Lack of cold temperatures is driving recent high-summer warming in the southern Rocky Mountains - M. C. A. Torbenson; E. Martinez del Castillo; F. Reinig; D. W. Stahle; K. E. King; J. T. Maxwell; G. L. Harley; E. Ziaco; J. Esper (International Journal of Biometeorology, 2025)
We present a 483-year-long tree-ring chronology from a high-elevation Engelmann spruce stand in central Colorado. Over 800,000 density measurements produce a maximum latewood density (MXD) record, which together with tree-ring widths, is used to assess the climatic influences on radial tree growth. Variability in MXD is strongly related to local and regional August maximum temperatures (T max ) for 127 years of overlapping instrumental climate data. A single-predictor reconstruction based on the MXD record explains > 50% of the variance in regional August T max is presented and considered robust for the period 1662–2021. The estimates of past temperature variability display phases of continuous cold conditions that are beyond the range of the instrumental record, including the 1830s. Our results further indicate that August T max have been higher since the early 1990s than for any other 30-year period in the past 350 years. This recent increase occurs on top of multi-centennial warming, and appears to be driven mainly by less frequent cold summers rather than an increase in warm extremes.

The effect of bovine diets and stages of lactation on vitamin K content in butter and Cheddar cheese - Sitong Zhou; Jean-Christophe Jacquier; Raquel Cama-Moncunill; Hannah Furlong; Gabriela Gonzales Castillo; Peter Dunne; Mark Timlin; Deirdre Hennessy; Michael O’Donovan; Kieran McCarthy; Tom F. O’Callaghan; John P. Murphy; et al. (International Dairy Journal, 2025)

Shortfalls in the protection of Important Shark and Ray Areas undermine shark conservation efforts in the Central and South American Pacific - Théophile L. Mouton; Adriana Gonzalez-Pestana; Christoph A. Rohner; Ryan Charles; Emiliano García-Rodríguez; Peter M. Kyne; Amanda Batlle-Morera; Giuseppe Notarbartolo di Sciara; Asia O. Armstrong; Enzo Acuña; Joanna Alfaro-Shigueto; Randall Arauz; et al. (Marine Policy, 2025)

Bacterial dynamics and volatile metabolome changes of vacuum-packaged beef with different pH during chilled storage - Magdevis Y. Rodriguez-Caturla; Larissa P. Margalho; Juliana S. Graça; Arthur K.R. Pia; Viny L. Xavier; Melline F. Noronha; Lucélia Cabral; Wilson J.F. Lemos-Junior; Carmen J.C. Castillo; Anderson S. SantˈAna (International Journal of Food Microbiology, 2025)

Impact of coagulation characteristics on the aggregation of microplastics in upper-ocean turbulence - F. Pizzi; M. Rahmani; C. Romera-Castillo; F. Peters; J. Grau; F. Capuano; L. Jofre (Advances in Water Resources, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gravimetric survey and modelling of a tectonic indenter boundary: The Palomares Fault Zone (Betic Cordillera, Iberia) - V. Tendero-Salmerón; G. Ercilla; L. González-Castillo; A. Madarieta-Txurruka; F.J. Martínez-Moreno; F. Estrada; J. Galindo-Zaldivar (Tectonophysics, 2024)

Hg and Se in Muscle and Liver of Blue Shark (Prionace glauca) from the Entrance of the Gulf of California: An Insight to the Potential Risk to Human Health - M. E. Rechimont; J. Ruelas-Inzunza; F. Amezcua; F. Paéz-Osuna; J. L. Castillo-Géniz (Archives of Environmental Contamination and Toxicology, 2024)

Surface activity of protein extracts from seed oil by-products and wettability of developed bioplastics - Seyedeh Fatemeh Mirpoor; Pablo F. Ibáñez-Ibáñez; C. Valeria L. Giosafatto; Teresa del Castillo-Santaella; Miguel A. Rodríguez-Valverde; Julia Maldonado-Valderrama (Food Hydrocolloids, 2023)

International Lima Bean Network: from the origin of the species to modern plant breeding - Jaime Martínez-Castillo; Ademir S. F. Araujo; María I. Chacón-Sánchez; Luis G. Santos; Angela C. A. Lopes; Kimberly Gibson; Regina L. F. Gomes; Rubén H. Andueza-Noh; Elena Bitochi; Horacio S. Ballina-Gómez; Eduardo Peralta; Ernesto Ormeño-Orrillo; et al. (Genetic Resources and Crop Evolution, 2023)

In Situ Radioactivity Maps and Trace Metal Concentrations in Beach Sands of a Mining Coastal Area at North Aegean, Greece - Christos Tsabaris; Dionisis L. Patiris; Rosalinda Adams; Julian Castillo; Maria F. Henriquez; Caroline Hurtado; Lesley Munoz; Leonidas Kalpaxis; Mariana Verri; Stylianos Alexakis; Filothei K. Pappa; Angelos Lampousis (Journal of Marine Science and Engineering, 2023)
In recent years, the environmental effects of both active and legacy mining activity have motivated many research groups worldwide through the use of a variety of methods that have been conducted among diverse environments. In this study, we measured radionuclide concentrations at two coastline locations of the Northern Aegean Sea: Stratoni and Ierissos. We deployed KATERINA II, an in situ gamma ray spectrometer. Our results indicate that the activity concentration for 238U progenies (214Bi), 232Th progenies (208Tl and 228Ac) and 40K vary by up to (33 ± 4) Bq kg−1, (19 ± 3) Bq kg−1, and (420 ± 30) Bq kg−1, respectively. The activity concentration of the 137Cs in Stratoni and Ierissos beach sands were (8.1 ± 2.2) and (3.9 ± 1.2) Bq kg−1, respectively. Lab-based measurements were also collected prior to the in situ data collection for the determination of radionuclide and metal concentrations. The lab-based data were found to be (800 ± 40) μg g−1 and (12 ± 1) μg g−1, for As, (1200 ± 60) μg g−1 and (33.3 ± 0.3) μg g−1 for Pb, (100 ± 6) μg g−1 and (6.0± 0.3) μg g−1 for Cu and (2000 ± 60) μg g−1 and (8.0 ± 0.4) μg g−1 for Zn, respectively. We used the R language and environment for statistical computing to produce radiological maps of the subject beach sands. We used the Enrichment Factor (EF) to estimate assessment indices for the target area and compared them to internationally recommended values. The in situ maps will be discussed since the beach area of the load-out pier area of Stratoni was undergoing the first phase of active remediation. We conclude that the temporal aspect of this dataset can be of significant reference value against future comparative studies after the remediation of the Stratoni beach with potentially denser spatial and temporal data coverage.

Lactoferrin gene polymorphisms associated with clinical mastitis in Honduran Holstein inheritance cows - M. Moncada-Laínez; P. A. Valladares-Medina; R. Castillo; X. F. De la Rosa-Reyna; A. M. Sifuentes-Rincón; V. R. Moreno-Medina; A. L. Lara-Rivera; G. M. Parra-Bracamonte (Molecular Biology Reports, 2023)

Extinction risk, reconstructed catches and management of chondrichthyan fishes in the Western Central Atlantic Ocean - Brendan S. Talwar; Brooke Anderson; Cristopher G. Avalos‐Castillo; María del Pilar Blanco‐Parra; Alejandra Briones; Diego Cardeñosa; John K. Carlson; Patricia Charvet; Charles F. Cotton; Zoe Crysler; Danielle H. Derrick; Michael R. Heithaus; et al. (Fish and Fisheries, 2022)
Chondrichthyan fishes are among the most threatened vertebrates on the planet because many species have slow life histories that are outpaced by intense fishing. The Western Central Atlantic Ocean, which includes the Greater Caribbean, is a hotspot of chondrichthyan biodiversity and abundance, but has been characterized by extensive shark and ray fisheries and a lack of sufficient data for effective management and conservation. To inform future research and management decisions, we analysed patterns in chondrichthyan extinction risk, reconstructed catches and management engagement in this region. We summarized the extinction risk of 180 sharks, rays and chimaeras, including 66 endemic and 14 near‐endemic species, using contemporary IUCN Red List assessments. Over one‐third (35.6%) were assessed as Vulnerable, Endangered or Critically Endangered, primarily due to overfishing. Reconstructed catches from 1950 to 2016 peaked in 1992, then declined by 40.2% thereafter. The United States, Venezuela and Mexico were responsible for most catches in the region and hosted the largest proportions of the regional distributions of threatened species, largely due to having extensive coastal habitats in their Exclusive Economic Zones. The quantity and taxonomic resolution of fisheries landings data were poor in much of the region, and national‐level regulations varied widely across jurisdictions. Deepwater fisheries represent an emerging threat, although many deepwater chondrichthyans currently have refuge beyond the depths of most fisheries. Regional collaboration as well as effective and enforceable management informed by more complete fisheries data, particularly from small‐scale fisheries, are required to protect and recover threatened species and ensure sustainable fisheries.

Delineation of blacktip shark ( Carcharhinus limbatus ) nursery habitats in the north‐western Gulf of Mexico - Philip Matich; Camryn L. Bigelow; Barrett Chambers; Jillian J. Dodds; Jessica A. Hebert; Alexis Lemieux; Christy M. Pittman; Julianna Trapp; Brooke Bianco; Carolina P. Cadena; Emily I. Castillo; Gabriela I. Castillo; et al. (Journal of Fish Biology, 2022)
Coevolution with predators leads to the use of low‐risk habitats by many prey species, which promotes survival during early developmental phases. These nurseries are valued by conservation and management agencies because of their contributions to adult populations. However, the physical and geographic characteristics, like shallow depths and isolation from other marine habitats, that restrict access to predators and thereby reduce risk to juvenile animals can also limit scientific research. Consequently, many nursery habitats are still unidentified and understudied. Here we used gillnet monitoring from 1982 to 2018 to delineate blacktip shark ( Carcharhinus limbatus ) nurseries in the north‐western Gulf of Mexico and elucidated their physical, environmental and biological characteristics. Nursery habitats within estuaries (

Probiotic Properties of Alcaligenes faecalis Isolated from Argyrosomus regius in Experimental Peritonitis (Rat Model) - A. I. Gutiérrez-Falcón; A. M. Ramos-Nuez; A. Espinosa de los Monteros y Zayas; D. F. Padilla Castillo; M. Isabel García-Laorden; F. J. Chamizo-López; F. Real Valcárcel; F. Artilles Campelo; A. Bordes Benítez; P. Nogueira Salgueiro; C. Domínguez Cabrera; J. C. Rivero-Vera; et al. (Probiotics and Antimicrobial Proteins, 2021)
A strain of Alcaligenes faecalis A12C ( A. faecalis A12C) isolated from Argyrosomus regius is a probiotic in fish. Previous experiments showed that A. faecalis A12C had inhibitory effects on the growth of multidrug-resistant bacteria. We aimed to confirm whether A. faecalis A12C is safe and has adequate intestinal colonization in experimental rats, and evaluate its efficacy in an animal model of peritonitis . We used 30 male rats, randomly divided into 6 groups ( n = 5): three groups (HA7, HA15, HA30) received A. faecalis A12C in drinking water (6 × 10 8 CFU/mL) for 7 days, and three control groups received drinking water only. All groups were evaluated at 7, 15, and 30 days. Survival after A. faecalis A12C administration was 100% in all groups. Mild eosinophilia (1.5%, p < 0.01) and increased aspartate aminotransferase (86 IU/L, p < 0.05) were observed in HA7, followed by progressive normalization. No histological signs of organ injury were found. We observed significant E. coli decline in faeces, parallel to an increase in A. faecalis A12C at 7 days. E. coli had a tendency to recover initial values, while A. faecalis A12C disappeared from the intestinal microbiota at 30 days. To evaluate its efficacy against peritonitis, we studied two additional groups of animals: IA group pretreated with A. faecalis A12C before E. coli intra-abdominal inoculation, and IC group inoculated with no A. faecalis A12C. We found an increase in C-reactive protein, alanine aminotransferase, urea, and eosinophils in IC animals when compared with IA. Peritonitis was more evident in IC than in IA animals. Our findings suggest that A. faecalis A12C altered clinically relevant parameters in sepsis and was associated with a lesser spread of infection.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Resource availability and heterogeneity shape the self‐organisation of regular spatial patterning - Jessica A. Castillo Vardaro; Juan A. Bonachela; Christopher C. M. Baker; Malin L. Pinsky; Daniel F. Doak; Robert M. Pringle; Corina E. Tarnita (Ecology Letters, 2021)
Explaining large‐scale ordered patterns and their effects on ecosystem functioning is a fundamental and controversial challenge in ecology. Here, we coupled empirical and theoretical approaches to explore how competition and spatial heterogeneity govern the regularity of colony dispersion in fungus‐farming termites. Individuals from different colonies fought fiercely, and inter‐nest distances were greater when nests were large and resources scarce—as expected if competition is strong, large colonies require more resources and foraging area scales with resource availability. Building these principles into a model of inter‐colony competition showed that highly ordered patterns emerged under high resource availability and low resource heterogeneity. Analysis of this dynamical model provided novel insights into the mechanisms that modulate pattern regularity and the emergent effects of these patterns on system‐wide productivity. Our results show how environmental context shapes pattern formation by social‐insect ecosystem engineers, which offers one explanation for the marked variability observed across ecosystems.

Arsenic in Latin America: New findings on source, mobilization and mobility in human environments in 20 countries based on decadal research 2010-2020 - Jochen Bundschuh; Maria Aurora Armienta; Nury Morales-Simfors; Mohammad Ayaz Alam; Dina L. López; Valeria Delgado Quezada; Sebastian Dietrich; Jerusa Schneider; Joseline Tapia; Ondra Sracek; Elianna Castillo; Lue-Meru Marco Parra; et al. (Critical Reviews in Environmental Science and Technology, 2021)

The virus–host interface: Molecular interactions of Alphacoronavirus‐1 variants from wild and domestic hosts with mammalian aminopeptidase N - Ximena A. Olarte‐Castillo; Joana F. dos Remédios; Felix Heeger; Heribert Hofer; Stephan Karl; Alex D. Greenwood; Marion L. East (Molecular Ecology, 2021)
The Alphacoronavirus ‐ 1 species include viruses that infect numerous mammalian species. To better understand the wide host range of these viruses, better knowledge on the molecular determinants of virus–host cell entry mechanisms in wildlife hosts is essential. We investigated Alphacoronavirus ‐ 1 infection in carnivores using long‐term data on Serengeti spotted hyenas ( Crocuta crocuta ) and molecular analyses guided by the tertiary structure of the viral spike (S) attachment protein's interface with the host receptor aminopeptidase N (APN). We sequenced the complete 3′‐end region of the genome of nine variants from wild African carnivores, plus the APN gene of 15 wild carnivore species. Our results revealed two outbreaks of Alphacoronavirus ‐ 1 infection in spotted hyenas associated with genetically distinct canine coronavirus type II (CCoVII) variants. Within the receptor binding domain (RBD) of the S gene the residues that directly bind to the APN receptor were conserved in all variants studied, even those infecting phylogenetically diverse host taxa. We identified a variable region within RBD located next to a region that directly interacts with the APN receptor. Two residues within this variable region were under positive selection in hyena variants, indicating that both sites were associated with adaptation of CCoVII to spotted hyena APN. Analysis of APN sequences revealed that most residues that interact with the S protein are conserved in wild carnivores, whereas some adjacent residues are highly variable. Of the variable residues, four that are critical for virus–host binding were under positive selection and may modulate the efficiency of virus attachment to carnivore APN.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Development of nuclear microsatellite markers to facilitate germplasm conservation and population genetics studies of five groups of tropical perennial plants with edible fruits and shoots: rambutan (Nephelium lappaceum L.), sapodilla (Manilkara zapota (L.) P. Royen), lychee (Litchi chinensis Sonn.), mangosteen (Garcinia mangostana Linn. and Garcinia cochinchinensis (Lour.) Choisy) and bamboo (Bambusa vulgaris Schrad. ex J.C. Wendl and Guadua angustifolia Kunth) - Renée S. Arias; Linda L. Ballard; Mary V. Duke; Sheron A. Simpson; Xiaofen F. Liu; Valerie A. Orner; Victor S. Sobolev; Brian E. Scheffler; Jaime Martinez-Castillo (Genetic Resources and Crop Evolution, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Hedgehog signaling promotes angiogenesis directly and indirectly in pancreatic cancer - Dirk Bausch; Stefan Fritz; Louisa Bolm; Ulrich F. Wellner; Carlos Fernandez-del-Castillo; Andrew L. Warshaw; Sarah P. Thayer; Andrew S. Liss (Angiogenesis, 2020)

Supporting Spartina : Interdisciplinary perspective shows Spartina as a distinct solid genus - Alejandro Bortolus; Paul Adam; Janine B. Adams; Malika L. Ainouche; Debra Ayres; Mark D. Bertness; Tjeerd J. Bouma; John F. Bruno; Isabel Caçador; James T. Carlton; Jesus M. Castillo; Cesar S. B. Costa; et al. (Ecology, 2019)
In 2014, a DNA‐based phylogenetic study confirming the paraphyly of the grass subtribe Sporobolinae proposed the creation of a large monophyletic genus Sporobolus , including (among others) species previously included in the genera Spartina , Calamovilfa , and Sporobolus. Spartina species have contributed substantially (and continue contributing) to our knowledge in multiple disciplines, including ecology, evolutionary biology, molecular biology, biogeography, experimental ecology, biological invasions, environmental management, restoration ecology, history, economics, and sociology. There is no rationale so compelling to subsume the name Spartina as a subgenus that could rival the striking, global iconic history and use of the name Spartina for over 200 yr. We do not agree with the subjective arguments underlying the proposal to change Spartina to Sporobolus . We understand the importance of both the objective phylogenetic insights and of the subjective formalized nomenclature and hope that by opening this debate we will encourage positive feedback that will strengthen taxonomic decisions with an interdisciplinary perspective. We consider that the strongly distinct, monophyletic clade Spartina should simply and efficiently be treated as the genus Spartina .

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Design, synthesis and in vitro evaluation of a Dopa-organoboron compound that acts as a bladder relaxant through non-catecholamine receptors - Ana L. Ocampo-Néstor; Ruth M. López-Mayorga; Enrique F. Castillo-Henkel; Itzia I. Padilla-Martínez; José G. Trujillo-Ferrara; Marvin A. Soriano-Ursúa (Molecular Diversity, 2019)

Lower tier toxicity risk assessment of agriculture pesticides detected on the Río Madre de Dios watershed, Costa Rica - M Arias-Andrés; R Rämö; F Mena Torres; R Ugalde; L Grandas; C Ruepert; L E Castillo; P J Van den Brink; J S Gunnarsson (Environmental Science and Pollution Research, 2018)

Impact of activated sludge acclimation on the biodegradation of toluene absorbed in a hydrophobic ionic liquid - A. S. Rodriguez Castillo; S. Guihéneuf; P.-F. Biard; L. Paquin; A. Amrane; A. Couvert (International Journal of Environmental Science and Technology, 2018)

Estimation of natural outcrossing rate and genetic diversity in Lima bean (Phaseolus lunatus L. var. lunatus) from Brazil using SSR markers: implications for conservation and breeding - J. S. Penha; A. C. A. Lopes; R. L. F. Gomes; J. B. Pinheiro; J. R. Assunção Filho; E. A. Silvestre; J. P. G. Viana; J. Martínez-Castillo (Genetic Resources and Crop Evolution, 2017)

Predictive score of haematological toxicity in patients treated with linezolid - J. González-Del Castillo; F. J. Candel; R. Manzano-Lorenzo; L. Arias; E. J. García-Lamberechts; F. J. Martín-Sánchez (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Effects of feeding ground pods of Enterolobium cyclocarpum Jacq. Griseb on dry matter intake, rumen fermentation, and enteric methane production by Pelibuey sheep fed tropical grass - S. Albores-Moreno; J. A. Alayón-Gamboa; A. J. Ayala-Burgos; F. J. Solorio-Sánchez; C. F. Aguilar-Pérez; L. Olivera-Castillo; J. C. Ku-Vera (Tropical Animal Health and Production, 2017)

Application of Focused Ultrasound-Assisted Extraction to the Determination of Persistent Organic Pollutants (POPs) in Soil Samples - R. Flores-Ramírez; S. E. Medellín-Garibay; C. G. Castillo; C. A. Ilizaliturri-Hernández; B. A. Zuki-Orozco; L. Batres-Esquivel; F. Díaz-Barriga (Bulletin of Environmental Contamination and Toxicology, 2015)

Biochemical, Physical, Chemical, and Microbiological Assessment of Blue Shrimp ( Litopenaeus stylirostris ) Stored in Ice - Dalila F. Canizales-Rodríguez; Víctor M. Ocaño-Higuera; Enrique Marquez-Rios; Abril Z. Graciano-Verdugo; Jose L. Cárdenas-López; María S. Yepiz-Gómez; Francisco J. Castillo-Yáñez (Journal of Aquatic Food Product Technology, 2015)

Muscular strength and markers of insulin resistance in European adolescents: the HELENA Study - D. Jiménez-Pavón; F. B. Ortega; J. Valtueña; J. Castro-Piñero; S. Gómez-Martínez; M. Zaccaria; F. Gottrand; D. Molnár; M. Sjöström; M. González-Gross; M. J. Castillo; L. A. Moreno; et al. (European Journal of Applied Physiology, 2012)

Seismic risk analysis of urban non-engineered buildings: application to an informal settlement in Mérida, Venezuela - A. Castillo; F. López-Almansa; L. G. Pujades (Natural Hazards, 2011)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Introgression in the genus Salmo via allotriploids - A. G. F. CASTILLO; E. BEALL; P. MORAN; J. L. MARTINEZ; F. AYLLON; E. GARCIA‐VAZQUEZ (Molecular Ecology, 2007)
Hybridization between sympatric species is not uncommon in the wild. Wild allotriploids (individuals with two chromosome sets from a species + one chromosome set from another species) are generally the result of a backcross between interspecific hybrids that produce unreduced gametes and one of the parental species. In animals, allotriploids are commonly sterile, except for some vertebrate species complexes in which allotriploids reproduce by parthenogenesis, gynogenesis and/or hybridogenesis, producing generally clonal or hemiclonal gametes; nuclear DNA introgression between hybridizing species is considered to be extremely rare. Employing species‐specific molecular markers, we show genetic introgression between the chromosomally well‐differentiated salmonids Atlantic salmon (2n = 58) and brown trout (2 n = 80) through spontaneous bisexual reproduction of allotriploids leading to salmon‐like offspring bearing some brown trout genes. Although introgression between these Salmo species can occur via allotriploids, we hypothesize that extinction of parental species can be discarded based on very low survival of allotriploid offspring.

Early effects of tillage and crop rotation on arbuscular mycorrhizal fungal propagules in an Ultisol - C. G. Castillo; R. Rubio; J. L. Rouanet; F. Borie (Biology and Fertility of Soils, 2006)

Interactions Between Nitrate Assimilation and 2,4-Dinitrophenol Cometabolism in Rhodobacter capsulatus E1F1 - V.M. Luque-Almagro; R. Blasco; L. Paloma Sáez; M. D. Roldán; C. Moreno-Vivián; F. Castillo; M. Martínez-Luque (Current Microbiology, 2006)

Cattle as Biomonitors of Soil Arsenic, Copper, and Zinc Concentrations in Galicia (NW Spain) - M. López Alonso; J. L. Benedito; M. Miranda; C. Castillo; J. Hernández; R. F. Shore (Archives of Environmental Contamination and Toxicology, 2002)

Astrovirus Infection Among Children with Gastroenteritis in the City of Zaragoza, Spain - L. López; F. J. Castillo; M. A. Fernández; A. Clavel; M. C. Rubio; R. Gómez-Lus; B. Cutillas (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Use of a Selective Medium and a Membrane Filter Method for Isolation of Campylobacter Species from Spanish Paediatric Patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Use of a selective medium and a membrane filter method for isolation ofCampylobacter species from Spanish paediatric patients - L. López; F. J. Castillo; A. Clavel; M. C. Rubio (European Journal of Clinical Microbiology & Infectious Diseases, 1998)